2003
DOI: 10.1186/1468-6708-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a comprehensive cardiac rehabilitation program on quality of life and exercise tolerance in women: A retrospective analysis

Abstract: Background: Currently, there are a lack of investigations that have examined the effect of participating in a comprehensive cardiac rehabilitation program on quality of life and physiological measures in women of different ages. The purpose of this investigation was to examine the effect of participating in a comprehensive cardiac rehabilitation program on quality of life, exercise tolerance, blood pressure and lipids in women between 33 and 82 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 22 publications
3
28
0
2
Order By: Relevance
“…Mostafavi et al found that women had greater improvements in terms of mental health and the constraints were caused by physical problems [24]. In general, it can be attributed to the lower initial quality level of females and their exercise capacity compared to males [25,26]. The findings of the present study also approve the Merkris's results.…”
Section: Discussionsupporting
confidence: 82%
“…Mostafavi et al found that women had greater improvements in terms of mental health and the constraints were caused by physical problems [24]. In general, it can be attributed to the lower initial quality level of females and their exercise capacity compared to males [25,26]. The findings of the present study also approve the Merkris's results.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, however, age and medical baseline variables were well balanced between men and women. In two other investigations specifically addressing the effectiveness of lifestyle modification and comprehensive cardiac rehabilitation in women, the intervention improved some psychosocial endpoints and QoL [49, 50]. In the M-HART trial the individually tailored program was only marginally significant in reducing symptoms of anxiety and depression for men and had no impact on psychological symptoms in women.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 100 women would be required to enroll in the study to have 70 women (approximately 35 per group) assessable for the primary endpoints. Based on Wilcoxon rank sum tests with 2-sided significance levels of .05 for each endpoint, there was 80% power to detect differences between the intervention arms of 1) 18.6 in the physical functioning score and 2) 1.2 minutes in exercise tolerance, given variability estimates of 22 minutes 8 and 2.4 minutes, 20 respectively, for changes in physical functioning and exercise tolerance.…”
Section: Discussionmentioning
confidence: 99%